PLXNC1 Enhances Carcinogenesis Through Transcriptional Activation of IL6ST in Gastric Cancer - Chen, Jie; Liu, Haining; Chen, Jinggui; Sun, Bo; Wu, Jianghong; Du, Chunyan (Frontiers in Oncology, 2020)
Background: Transcriptional factors (TFs) are responsible for orchestrating gene transcription during cancer progression. However, their roles in gastric cancer (GC) still remain unclear. Methods: We analyzed the differential expression of TFs and investigated plexin C1 (PLXNC1) RNA levels, its clinical relevance and functional mechanisms using GC cells and tissues. The molecular function of PLXNC1 was evaluated in vitro and in vivo. Kaplan-Meier curves and the log-rank test were used to analyze overall survival (OS) and disease-free survival (DFS). Results: PLXNC1 was frequently upregulated in GC and associated with poor prognosis. The expression level of PLXNC1 could serve as an independent biomarker to predict the patients’ overall survival. Notably, knockdown of PLXNC1 significantly abolished GC cells proliferation, and migration and overexpression of PLXNC1 accelerated carcinogenesis in GC. The gene set enrichment analysis (GSEA) indicated that high-expression of PLXNC1 was positively correlated with the activation of epithelial-mesenchymal transition (EMT), TNF-α, and IL-6/STAT3 signaling pathways. PLXNC1 promoted proliferation and migration of GC cells through transcriptional activation of interleukin 6 signal transducer (IL6ST), which could rescue the malignant behavior of PLXNC1 deficient GC cells. Conclusions: Our study demonstrated that the PLXNC1 plays oncogenic role in GC patients. PLXNC1-IL6ST axis represents a novel potential therapeutic target for GC.